Development of the pivoting system of the turning conveyor - Asmagambet Д.; Beisembayev М.; Zhetesova Г.С.; Malybaev Н.С. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2021)
The application of simulation modeling methods for the design of transport systems and conveyors with the rotation of lattices in the plane of the transportation surface due to rotary and rotarytranslational hinges is carried out in the Adams dynamic programming package based on Lagrange–Euler theory and using finite element technologies. As a result, the work of the conveyors can now be carried out in 3D. Such capabilities are necessary when entering the conveyor into the chamber after the tunneling combine and for transportation along with curved workings. It is also possible to use armored turning conveyors for the extraction of DBO ores. The above expressions consider the rotation of the conveyor’s lattices in any zone of its installation at a given angle up to 15о and allow determining its position in the chamber, taking into account the system of special hinges located on the sides of the lattices. The features of the movement of the combine as accelerated at short intervals of the route and the model of the turning process are substantiated.